(untitled) (One Health & Risk Management, 2023)
Introduction. The most important risk factors for lung cancer are the tobacco smoking and residential radon exposure. The study of the interaction of smoking x radon as trigger factor for lung cancer morbidity in the Republic of Moldova was carried out. Material and methods. Data on tobacco smoking prevalence of the national study STEPS 2021, lung cancer morbidity data of 2012-2020 and data of radon measurements using RADTRAK2 during 2018-2021 were used. Data processing tools included summary statistics and cluster analysis. Results. The distribution of high radon values, the number of smokers and the lung cancer morbidity is uneven throughout the country. The formation of higher cluster combining all variables has proceeded by the formation of two clusters: 1. lung cancer incidence, lung cancer prevalence, number of total tobacco smokers, number of male smokers, number of female smokers, and number of urban smokers, 2. radon concentration and number of rural smokers. Conclusions. Study results demonstrate the leading role of tobacco smoking on morbidity among the adult population, regardless of gender in an urban environment with a rather low concentration of radon, and at the same time indicate the cumulative effect of smoking and increased radon concentration in rural areas due to the construction features of houses and lifestyle.